The Relationship of Work Motivation, Work Discipline and Personal Characteristics of Nurses in Regional General Hospitals - Retno Kusumaningrum; Nur Jannah Nasution; Putu Agus Eka Rismawan; Merissa Fermica Iskandar; Muhammad Fatkhurohman Albashori (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to ascertain how work motivation and work discipline interact. 50 respondents made up the sample for this investigation, which used a cross-sectional study design. Chi square is the statistical test employed. The researcher used a study tool in the form of a questionnaire for the independent variables, which were work motivation and individual characteristics. The work discipline assessment form, which is completed by the managers of the work unit under study, and the document review form are used by the researcher even though work discipline is the dependent variable. 35% of the workforce had poor work discipline. Meanwhile, 65% of employees exhibit strong work discipline. Work motivation, employee traits, and workplace discipline do not significantly correlate. However, job motivation, reward or recognition, pay or wages or rewards, working circumstances, and work discipline have a substantial relationship.